A revised Red List of British butterflies. Issue 5 (25th May 2022) - Fox, Richard; Dennis, Emily B.; Brown, Andrew F.; Curson, Jon
Abstract: Regular reassessment of extinction risk is critical to prioritise conservation action during the current period of rapid, anthropogenic biodiversity change. Butterflies are a flagship group for insect monitoring and conservation, as they are highly visible, well studied and exhibit rapid responses to environmental change. Here, we use systematic population monitoring data from the UK Butterfly Monitoring Scheme and citizen‐science derived occurrence records to provide an updated assessment of extinction risk in Great Britain (GB) by applying current International Union for Conservation of Nature (IUCN) criteria to 62 butterfly species. The resulting regional Red List categorises four species as Regionally Extinct, 24 (41% of the remaining, extant species) as threatened (8 Endangered and 16 Vulnerable), 5 (9%) as Near Threatened and 29 (50%) as Least Concern. Recent reduction in population size (Criterion A) based on smoothed, long‐term time series of abundance and occurrence data, was responsible for most of the threatened or Near Threatened categorisations. While the status of some species improved, likely due to conservation efforts, the revised Red List demonstrates an ongoing deterioration in the status of GB butterflies, with a 26% increase in threatened species since the previous assessment. A greater proportion of butterflies was classed as threatened than for most other GB taxa. While this may stem from greater data availability for butterflies than most other groups (thus allowing tests of extinction risk against more criteria), it highlights the need to reinvigorate conservation efforts for these charismatic insects. Abstract : We present a new Red List of butterflies in Great Britain (GB) based on systematic monitoring data and citizen science observations. Four species are categorised as Regionally Extinct, 24 (41% extant species) as threatened (8 Endangered and 16 Vulnerable), 5 (9%) as Near Threatened and 29 (50%) as Least Concern. The revised Red List demonstrates an ongoing deterioration in the status of GB butterflies, with a 26% increase in threatened species since the previous assessment.